After 30 years of dissemination, have we achieved sustained practice change in motivational interviewing?. (28th July 2015) - Hall, Kate; Staiger, Petra K.; Simpson, Angela; Best, David; Lubman, Dan I.
Abstract: Aims: Motivational interviewing (MI) is the most successfully disseminated evidence‐based practice in the substance use disorder (SUD) treatment field. This systematic review considers two questions relevant to policymakers and service providers: (1) does training in MI achieve sustained practice change in clinicians delivering SUD treatment; and (2) do clinicians achieve a level of competence after training in MI that impacts upon client outcomes? Methods: A systematic review was conducted and reported in line with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement, examining training outcomes for MI in the SUD treatment sector, and for clinicians working in a SUD treatment role. We determined a training method to have resulted in sustained practice change when over 75% of participants met beginning proficiency in MI spirit at a follow‐up time‐point. Results: Of the 20 studies identified, 15 measured training at a follow‐up time‐point using standard fidelity measures. The proportion of clinicians who reached beginning proficiency was either reported or calculated for 11 of these studies. Only two studies met our criterion of 75% of clinicians achieving beginning proficiency in MI spirit after training. Of the 20 studies identified, two measured client substance use outcomes with mixed results. Conclusions: A broad range of training studies failed to achieve sustained practice change in MI according to our criteria. It is unlikely that 75% of clinicians can achieve beginning proficiency in MI spirit after training unless competency is benchmarked and monitored and training is ongoing. The impact of training on client outcomes requires future examination.